Systems in Flames: Dynamic Coproduction of Social–Ecological Processes. (13th July 2022) - Cadenasso, Mary L; Rademacher, Anne M; Pickett, Steward T A
Abstract: Ecologists who study human-dominated places have adopted a social–ecological systems framework to recognize the coproduced links between ecological and social processes. However, many social scientists are wary of the way ecologists use the systems concept to represent such links. This wariness is sometimes due to a misunderstanding of the contemporary use of the systems concept in ecology. We aim to overcome this misunderstanding by discussing the contemporary systems concept using refinements from biophysical ecology. These refinements allow the systems concept to be used as a bridge rather than a barrier to social–ecological interaction. We then use recent examples of extraordinary fire to illustrate the usefulness and flexibility of the concept for understanding the dynamism of fire as a social–ecological interaction. The systems idea is a useful interdisciplinary abstraction that can be contextualized to account for societally important problems and dynamics.